Echo time dependence of biexponential and triexponential intravoxel incoherent motion parameters in the liver. Issue 2 (28th August 2021) - Führes, Tobit; Riexinger, Andreas Julian; Loh, Martin; Martin, Jan; Wetscherek, Andreas; Kuder, Tristan Anselm; Uder, Michael; Hensel, Bernhard; Laun, Frederik Bernd
Abstract : Purpose: Intravoxel incoherent motion (IVIM) studies are performed with different acquisition protocols. Comparing them requires knowledge of echo time (TE) dependencies. The TE‐dependence of the biexponential perfusion fraction f is well‐documented, unlike that of its triexponential counterparts f 1 and f 2 and the biexponential and triexponential pseudodiffusion coefficients D *, D 1 ∗, and D 2 ∗ . The purpose was to investigate the TE‐dependence of these parameters and to check whether the triexponential pseudodiffusion compartments are associated with arterial and venous blood. Methods: Fifteen healthy volunteers (19‐58 y; mean: 24.7 y) underwent diffusion‐weighted imaging of the abdomen with 24 b‐values (0.2‐800 s/mm 2 ) at TEs of 45, 60, 75, and 90 ms. Regions of interest (ROIs) were manually drawn in the liver. One set of bi‐ and triexponential IVIM parameters per volunteer and TE was determined. The TE‐dependence was assessed with the Kruskal‐Wallis test. Results: TE‐dependence was observed for f ( P < .001), f 1 ( P = .001), and f 2 ( P < .001). Their median values at the four measured TEs were: f : 0.198/0.240/0.274/0.359, f 1 : 0.113/0.139/0.146/0.205, f 2 : 0.115/0.155/0.182/0.194. D, D *, D 1 ∗, and D 2 ∗ showed no significant TE‐dependence. Their values were: diffusion coefficient D (10 −4 mm 2 /s): 9.45/9.63/9.75/9.41, biexponential D * (10 −2 mm 2 /s): 5.26/5.52/6.13/5.82, triexponential D 1 ∗ (10 −2 mm 2 /s): 1.73/2.91/2.25/2.51, triexponential D 2 ∗ (mm 2 /s): 0.478/1.385/0.616/0.846. Conclusion: f 1 and f 2 show similar TE‐dependence as f, ie, increase with rising TE; an effect that must be accounted for when comparing different studies. The diffusion and pseudodiffusion coefficients might be compared without TE correction. Because of the similar TE‐dependence of f 1 and f 2, the triexponential pseudodiffusion compartments are most probably not associated to venous and arterial blood.